The Influence of System Quality, Information Quality, Perceived Usefulness, and Perceived Ease of Use on the Actual Use of SIAPIK Applications for MSME Sustainability - Sri Anjarwati; Yolifiandri Yolifiandri; Magita Magita; Sigit Mareta; Lestari Lestari; Edy Suryadi; Rani Agustiani (Jurnal Price : Ekonomi dan Akuntasi, 2025)
This study aims to analyze the influence of system quality, information quality, and perceived ease of use on MSME performance through the implementation of the Financial Information Recording Application System (SIAPIK). MSMEs continue to face challenges in financial management due to the use of conventional recording systems and limited digital literacy. Therefore, digital financial applications are expected to improve financial management efficiency and business sustainability. This study applies the Technology Acceptance Model (TAM) approach using a quantitative research design. Data were collected through questionnaires distributed to MSME owners who use SIAPIK applications in Jakarta. The collected data were analyzed using Structural Equation Modeling (SEM) with WarpPLS software. The findings indicate that system quality and information quality positively and significantly influence perceived ease of use. In addition, perceived ease of use positively affects MSME performance. These results demonstrate that user-friendly and reliable financial applications contribute to improving financial management effectiveness, operational efficiency, and business sustainability among MSMEs.